Effects of general practitioner training and family support services on the care of home-dwelling dementia patients - Results of a controlled cluster-randomized study - Wunder Sonja; Lauterberg Jörg; Menn Petra; Großfeld-Schmitz Maria; Gräßel Elmar; Donath Carolin; Marx Peter; Ruckdäschel Stephan; Mehlig Hilmar; Holle Rolf (BMC, 2010)
Abstract Background More than 90% of dementia patients are cared for by their general practitioners, who are decisively involved in the diagnosis, therapy and recommendation of support services. Objective: To test whether special training of general practitioners alters the care of dementia patients through their systematic recommendation of caregiver counseling and support groups. Method 129 general practitioners enrolled 390 dementia patients and their informal caregivers in a prospective, three-arm cluster-randomized 2-year study. Arm A constituted usual care, in Arm B and C support groups and caregiver counseling (in Arm B one year after baseline, in Arm C at baseline) were recommended by the general practitioners. The general practitioners received arm-specific training. Diagnostic and therapeutic behavior of physicians was recorded at baseline. Informal caregivers were questioned in follow-up after 2 years about the utilization of support services. Results The diagnostic behavior of the general practitioners conforms to relevant guidelines. The procedure in newly-diagnosed patients does not differ from previously diagnosed patients with the exception of the rate of referral to a specialist. About one-third of the newly-diagnosed dementia patients are given an anti-dementia drug. The utilization of support groups and counseling increased five- and fourfold, respectively. Utilization of other support services remained low (< 10%), with the exception of home nursing and institutional short-term nursing. Conclusion Trained general practitioners usually act in conformity with guidelines with respect to diagnosing dementia, and partly in conformity with the guidelines with respect to recommended drug therapy. Recommendations of support services for informal caregivers by the general practitioner are successful. They result in a marked increase in the utilization rate for the recommended services compared to offers which are not recommended by the general practitioner. Trial registration ISRCTN68329593